2019
DOI: 10.2298/gensr1901167m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of spike length in wheat

Abstract: the geographical origin could not explain the grouping of genotypes within the same, so the division into two groups was done on the basis of their lines of descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…A large sum of squares for the environments indicated differences between the growing seasons and diversity of treatments caused a considerable sum of squares for environmental factors in the total variation, indicating that these factors were the most responsible for the variation of the spike length. A higher influence of environmental factor on the spike length was also observed by Zečević et al [ 30 ] and Mladenov et al [ 31 ].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A large sum of squares for the environments indicated differences between the growing seasons and diversity of treatments caused a considerable sum of squares for environmental factors in the total variation, indicating that these factors were the most responsible for the variation of the spike length. A higher influence of environmental factor on the spike length was also observed by Zečević et al [ 30 ] and Mladenov et al [ 31 ].…”
Section: Resultssupporting
confidence: 69%
“…Significant interactions between environment and wheat cultivars in spike length, as high share of the first two main components IPCA1 and IPCA2 in the GE variation have been reported by Brbaklić et al [ 32 ] and Mladenov et al [ 31 ]. According to the biplot ( Figure 2 a) and in terms of the average values ( Table 5 ), it can be noticed that, except for certain exceptions, all of the agroecological environments are quite near to the level of the experimental overall average.…”
Section: Resultsmentioning
confidence: 81%
“…In the AMMI model, the ANOVA separate additive effects from the interaction, while additional GEI analysis can be carried out by principle component analysis (PCA). The biplot graphic representation shows both the main and interaction effects for genotypes and environments simultaneously and provides analysis of the G × E interaction [ 22 , 36 , 40 , 41 ]. The IPCA1 score of a genotype in the AMMI analysis was used as an indicator of the stability of a genotype over environments [ 12 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects of high Na concentration in the B horizon on management practices and on seedbed preparation has been observed by Cairns [ 19 ], while adverse effect to the uptake of plant nutrients by the roots was observed by Peters [ 20 ] and Miller and Brierley [ 11 ]. Despite wheat being considered as basically grass, durable and more resistant to limiting factors in agricultural production than many other crops, the considerable decreases in yield and yield related traits have been observed in wheat production under stress conditions of halomorphic soils [ 5 , 21 , 22 ]. At the same time, global demand for wheat is estimated to increase by 2050, as a consequence of growing dietary requirements of an increasing world population [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of this study, there was a notable variation in GY and NUE among winter wheat cultivars when grown under different environmental conditions and soil N level. Similarly, many previous studies showed significant variation in small grain cereal GY between growing seasons and locations under conditions of the Pannonian plain (PRŽULJ et al, 2015;MLADENOV et al, 2018;MLADENOV et al, 2019). Generally, influence of the environmental conditions (season/location) is a major source of GY variation in different cereal crops, while effect of the others factors are less pronounced (MIROSAVLJEVIĆ et al, 2018).…”
Section: Discussionmentioning
confidence: 63%